ANALISIS LINTAS KARAKTER AGRONOMI TERHADAP KOMPONEN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Setyono; Rahmalia, Ratu; Yuliawati (Universitas Djuanda, 2023)
The peanut has been one of the most important commercial crops in Indonesia and its yield still needs to be improved. Peanut yield can be increased genetically through plant breeding programs. Indirect selection in peanut plant breeding programs requires information related to the relationship between its characters, especially the relationship between growth and yield characters through correlation and path analysis. This study aims to determine the relationship between growth and yield characteristics of peanuts based on correlation values, direct effects, and indirect effects using path analysis, so that selection criteria for high-yielding peanuts are obtained. This study was conducted using a survey method. 50 peanut plant samples were taken randomly as observation units, then path analysis was carried out. The results showed that the 12 DAP canopy width was positively and significantly correlated with peanut yield characters, such as fresh pod weight and number of pods. The 12 DAP canopy width also had the highest direct and indirect influence on the character of fresh and dry pod weight, and the number of pods. Indirect selection to increase peanut yield can be done using the 12 DAP canopy width character as selection criteria.